Trade tax reforms and poverty in developing countries: Why do some countries benefit and others lose? - Amèvi Rocard Kouwoaye (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper studies the relationship between trade tax and domestic tax reforms and poverty in developing countries, and explores whether the role of public goods provision matters in this relationship. Using a sample of 91 developing countries for the 1980-2016 period, I model the trade tax reforms-poverty nexus as heterogeneous across countries with cross-sectionally dependent errors. I find that a shift from taxes on international trade towards domestic taxes under revenue-neutrality reduces poverty in the countries that have consolidated, on average, over time their comparative advantage in agriculture, while it increases poverty in countries that moved from being net exporters to net importers of agricultural products. Public goods, however, do not play a significant role in the relationship.
Keywords: H2; F13; I38; C23; 330; common factor model; government spending; taxation and poverty; tradeliberalization; trade tax and domestic tax reforms